Pengaruh Edukasi Kesehatan dengan Penggunaan Metode Audiovisual tentang Sunting terhadap Pengetahuan Ibu di Kabupaten Cianjur Tahun 2023 - Sri Hartati; Papat Patimah; Rina Andriana Widianti (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Background: Stunting education is the process of conveying information and knowledge to individuals, especially mothers regarding stunting in toddlers. Stunting is a condition of growth failure in children under the age of five which is characterized by a shorter height than the standard that should be appropriate for their age. Stunting education aims to increase mothers' understanding and awareness about stunting, its causes, and the importance of fulfilling good nutrition to prevent and overcome stunting in children. Audiovisual methods are often used in stunting education, where information is conveyed through audio and visual media such as videos, presentations or animations. The use of audiovisual methods in stunting education has several advantages. First, this method can help mothers to better understand the information conveyed through an interesting combination of audio and visuals. Second, the use of pictures, graphics and animation can help mothers visualize the concepts and processes related to stunting. Third, this method can increase mothers' involvement and interest in acquiring knowledge about stunting. Purpose: This study aims to determine the effect of health education using audiovisual methods about stunting on mothers' knowledge in Cianjur district in 2023. Methods: The method used is the provision of health education through audio visuals and active discussion with 30 mothers. Knowledge data about stunting was collected using pretest and posttest questionnaires. Results: The results were obtained at the time of the pretest, respondents with good knowledge were 50%, sufficient knowledge was 30%, and knowledge was lacking by 20%. At the time of the posttest, respondents with good knowledge were 80%, 20% was sufficient, and 0% was lacking. Conclusion: There is an influence of health education using the audiovisual method about being able to increase the knowledge of families with toddlers about stunting at the Ciherang Working Area Health Center, Cianjur Regency in 2023. Further research needs to consider further monitoring and evaluation at a certain period of time to see the mother's memory abilities and attitudes who have stunted children. Suggestion: The plan for the next stage is to always increase the motivation of families with toddlers to always bring their children to integrated postal services (Posyandu) so that toddlers can be monitored in terms of nutrition and their development according to their age.